(untitled) (Construction Economics and Building, 2024)
Ireland is experiencing a national housing crisis, and this is replicated across many developed economies. This challenges governments and housebuilders to increase production whilst balancing challenging human resource and supply chain constraints. Lean construction methodologies have enhanced project delivery in other sectors of the industry. This study evaluates the outcomes of Last Planner System and Takt planning implementation on two residential projects. The study adopted a mixed methods approach utilising case study design and data collected from a literature review, site observation diary, site documentation analysis, and semi-structured interviews. Findings demonstrate schedule reduction opportunities through higher and more consistent PPC, reduction of cycle times, and enhanced adherence to start and finish dates. The study proposes a more holistic focus is needed on productivity improvement initiatives on the entire project scope as opposed to singular exercises on aspects like internal finishes alone. Increased inter-contractor communication and engagement led to a positive working environment with greater focus on the softer aspects of collaborative working. This study posits the discipline, detail, and diligence of Takt complements LPS to deliver an enhanced production-system that betters traditional schedule milestones in residential project delivery.